ON BIOLOGY OF TAC S US C TUS (V CIE S) FROM VE VAL - Raje, Sadashiv Gopal (Journal of Indian Fisheries Association, 2015)
The length-weight relationship of males and females of Tachysurus caelatuscan be described by the equation log W = -5.6659 + 3.2685 log L and log W =-4.7648 + 2.9104 log L, respectively. A sex ratio of 1.37 males : 1.00 females wasobserved. Fecundity in the fish measuring 385 to 402 mm ranges between 44and 55 ova. It is a demersal carnivorous feeder, fee g chiefly on crustaceans,fish, molluscs and polychaetes.Keywords: Tachysurus caelatus, length-weight relationship, sex ratio,fecundity, food and fee Â° g habit